Institutions and Creative Destruction in CEECs: Determinants of Inefficient Use of Assets - Jarko Fidrmuc; Martin Siddiqui (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyze the relationship between institutional quality and firm efficiency. Using rich data on firms in the European Union between 2005 and 2012, we show that high institutional quality lowers the share of persistently inefficiently used assets. The adverse effect of low institutional quality may be one of the narrow channels through which institutions affect income per capita in the long-run. Our approach combines institutional economics and Schumpeterian creative destruction. In addition, we observe similarities between inefficiently used assets by European firms and the phenomenon of zombie lending in Japan during the last decades.
Keywords: P43; K23; C33; 330